SISTEM PAKAR: DIAGNOSIS PENYAKIT UNGGAS DENGAN METODE CERTAINTY FACTOR - Rohajawati, Siti; Supriyati, Rina (Bina Nusantara University, 2010)
The development of expert systems–based applications has been very popular since 1950, with a rather wide coverage. Expert systems in organizations are aimed at adding value, increasing productivity and assisting management to take quick decisions. Similarly, organization engaging in the farming industry, while very promising, requires high awareness against diseases, such as poultry (chicken) which are very susceptible to various types of diseases caused by viruses or bacteria. Benefits of implementing the expert system are that they can diagnose the symptoms of diseases quickly and accurately and they are expected to be able to help farmers in anticipating the losses resulting from disease attack. Accurate and precise calculations are required to diagnose symptoms in order to conclude the output by means of the Certainty Factors (CFs)Keywords: expert system, diagnosing the diseases, method of Certainty Factors (CFs)